Formulation of enteric coated microspheres containing pantoprazole - Xuan Truong Le; Hue Minh Nguyen; Ngoc Quynh Le; Thi Thu Loan Trinh; Van Thanh Tran (Vietnam Journal of Science, Technology and Engineering, 2021)
Pantoprazole, a primary proton pump inhibitor used to manage gastric acid secretion disorders, is recognized for its minimal adverse effects and limited drug interactions. Enhancing its stability within gastric acid, delayed-release microspheres containing pantoprazole were developed through emulsification-solvent evaporation. This process utilized a polymer blend comprising hydroxypropyl cellulose (HPC) and ethyl cellulose (EC), subsequently coated with alginate and Eudragit® L100. The microspheres’ morphology was assessed using SEM, while laser diffraction facilitated the determination of particle size distribution. The physical state of the drug substance was analyzed through Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC), alongside in vitro drug release studies. Selected microsphere formulations exhibited an average size of 100 μm. Dissolution profiling revealed that less than 10% of the drug was released after 120 minutes in 0.1-M HCl, whereas over 75% of the drug was released within 45 minutes in a phosphate buffer with a pH of 6.8. This research demonstrates the potential of tailored microsphere formulations to optimize drug release kinetics and improve therapeutic outcomes for pantoprazole administration.